TEXT AS MEDIA, MATERIAL, AND LEARNING RESOURCES OF LITERATION TO DEVELOP A STUDENT CRITICAL THINKING ABILITY INSIDE THE DEVELOPMENT OF THE NATIONS - Nurchasanah Nurchasanah; Zakia Habsari (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
In literacy learning, the text has multiple roles. Many teachers worry about text positions in literacy learning. The text acts as a learning medium if it works directly as a messenger of learning that makes students easier to learn. For that purpose, the text needs to be modified, manipulated, and given a special identity in accordance with the interests of learning. The text acts as a learning material if the text serves as an object learned in learning. In order for the text to serve as a learning material, the text needs to be identified, analyzed, and interpreted in accordance with the learning objectives. The text also serves as a learning resource if the text serves as the source of the content of the material learned in the study. For this purpose, the textreveals its original form without any changes and treatment. Regardless of the role of the text in learning, the text can function to develop students' critical thinking skills so they can welcome and play a role in nation building. In order for the text to have a role it can train students to think critically; the form, treatment, and function of the text need to be differentiated.